Performance Evaluation of FDDI Network Using Synchronous Traffic - Kolan De Velu, Saravanan (2000)
This research project is to evaluate the network performance of fiber distributed data interface (FDDI) protocol with real-time application. In the real-time application, on-time delivery of messages is essential. Thus, a suitable media access protocol is needed to transmit both real-time and non real-time traffic simultaneously. A real-time data imposes specific delay requirements, either due to network control or reconstruction constraints. The performance study of FDDI protocol is carried throughout the simulation. Furthermore, the performance metrics such as average access delay, average message delay and maximum delay are examined in the simulation. The various target token rotation time (TTRT) values are investigated in this research. The real-time multimedia workload is complemented with non realtime traffic in the FDDI network. The real-time traffic is a periodic workload such as VOIce communication and video conferencing. Non real-time workloads are used as background traffic such as file transfer and interactive terminal. The results show that synchronous packets can be successfully complemented with asynchronous packets in the FDDI network. The TTRT values of two to four milliseconds ensure optimal network performance over huge data transfer rates. This research helps to understand the protocol behaviour toward different data traffic patterns and proposes an optimal value for TTRT in the real-time implementation.